The Hitchhiker’s Guide to Organophosphate Chemistry - Jessen, H. J. (Synlett, 2018)
Phosphate esters and anhydrides are abundant motifs in biologically important molecules. Their chemical synthesis, modification, and purification are still challenging tasks often restricted to specialized laboratories. The isolation and analytical characterization of novel highly charged (poly)phosphorylated natural products comes with many challenges but also opportunities. Understanding the in vivo function of such molecules is another central endeavor. More often than not, studies into the function of charged metabolites are hampered by insufficient cellular uptake and thus delivery technologies are in high demand. Overall, research in this field requires several complementary approaches. This account discusses selected examples of some emerging technologies in organophosphate chemistry, with a focus on recent achievements in the authors laboratory usually in the context of diverse collaborative efforts.1 Prologue2 Introduction3 The Inositol Phosphates and Pyrophosphates3.1 Novel Synthetic Approaches3.2 Stereochemical Assignment3.3 A Protecting Group Concept for Phosphates3.4 Cellular Delivery3.5 Selected Examples of New Biology4 Nucleotides4.1 Iterative Phosphorylation4.2 Bidirectional Phosphorylation5 Conclusion6 Outlook
Keywords: phosphorylation; inositol pyrophosphates; nucleotides; chemical biology; chiral solvating agents; phosphate homeostasis